The Direct Gene Injection Using of Egg Yolk Emulsion as Carrier and its Comparison with Liposomes. - Baghdad Science Journal (مجلة بغداد للعلوم)
The efficiency of egg yolk emulsion in coating DNA and its delivery across cellular membranes was evaluated in comparison with liposomes DOPE . The murine leukemia viral oncogene v-abl , cloned on pBR322 was used as a DNA substrate for direct injection into mice tissue . the DNA complexes were prepared by mixing the DNA with egg yolk emulsion and liposome . Each was directly injected into mice peritoneal cavity with proper control. The gene delivery was examined phenotypically by blood analysis and cytogenetic analysis . Chromosomal changes were detected in the bone marrow as from the fourth day post inoculation through the eleventh day when chromosomal ring s could be seen . this was accompanied by decrease in the WBC count , an increase in lymphoblast cells size and percentage and the discoloration of irregular RBCs . these are typical signs of acute lymphatic leukemia . Anatomical examination have indicated 25% increase in the spleen mplemented using specific primers to confirm the integration of the delivered DNA into the genomic content of the mice tissue within 48 hr post inoculation .